الصلاح والأصلح عند المعتزلة والماتريديّة: دراسة مقارنة بين الزّمخشريّ في الكشاف والنّسفيّ في مدارك التنزيل: AL-SALAH WA AL-ASLAH ACCORDING TO AL-MU’TAZILAH AND AL-MATURIDIYYAH: A COMPARATIVE STUDY BETWEEN AL-ZAMAKHSHARI IN AL-KASHSHAF AND AL-NASAFI IN MADARIK AL-TANZIL - Syed Abdul Rahman, Syed Mohammad Hilmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
Al-Salah wa al-Aslah is the subject of debate between al-Mu’tazilah and al-Maturidiyyah. It was also discussed by al-Zamakhshari in al-Kashshaf and al-Nasafi in Madarik al-Tanzil. This paper uses the method of data collection and comparative analysis to discuss the general concept of al-Salah wa al-Aslah according to al-Mu’tazilah and al-Maturidiyyah by making comparisons between the two figures. The study found that al-Zamakhshari agreed with the majority of al-Mu`tazilah who said that al-Salah wa al-Aslah is obligatory to Allah SWT based on the law of reason which decides that the wisdom of His actions leads to the obligation to protect the maslahah of the servant. Although al-Nasafi and al-Maturidiyyah agreed that Allah’s SWT actions have wisdom, al-Nasafi did not agree that Allah is obliged to al-Salah wa al- Aslah. This is because all the acts of Allah are right and the servants have no right to dispute it.